Powers of the Constitutional Court to Interpret its Formerly Adopted Ruling, Conclusion or Decision: Problems of Legal Regulation and Possibilities for their Improvement - Pūraitė-Andrikienė, Dovilė (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English] This article attempts to reveal the problems of the provisions regulating the institution of the interpretation of a formerly adopted ruling, conclusion or decision of the Constitutional Court of the Republic of Lithuania and to present the posibilities of their solution, i. e., proposals on how to improve the provisions of the Law on the Constitutional Court regulating this institution.This work mainly focuses on three problematic aspects of this institution: the legal force of the decisions on the interpretation of a ruling, conclusion or decision of the Constitutional Court; the objects of this institution; subjects entitled to initiate the interpretation of a ruling, conclusion or decision of the Constitutional Court.